Impacts of photography and immersive imaging on tourism : a case study on Mulu National Park - Lee, Hui Khoon (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The emerging of quick time virtual reality (QTV) and the heritage industry have played important roles in the touism industry. It is a new interactive-based technology to enhance a destination appeal. It has become a powerful marketing tool to educational, enviromental, economical, social and psychological impacts in heritage preservation in both domestic and international levels. Attention was given to the real-time based rendering in Gunung Mulu National Park which aspires to protect such places from enviromental decay as well as natural disasters, with technical solutions. The OTVR can be created by 'stitching' together overlappig photographs from different positions and oientations. The capabilities of QTVR highlighted some of its potential uses in the industry and addressing some of its shortcomings. In addition, a few future developments in preserving our World Heritaage through virtual envioment are identified.